Effect of Monthly High-Dose Vitamin D Supplementation on Acute Respiratory Infections in Older Adults: A Randomized Controlled Trial. (17th August 2019) - Camargo, Carlos A; Sluyter, John; Stewart, Alistair W; Khaw, Kay-Tee; Lawes, Carlene M M; Toop, Les; Waayer, Debbie; Scragg, Robert
Abstract: Background: Although adults with low vitamin D status are at increased risk of acute respiratory infection (ARI), randomized controlled trials of vitamin D supplementation have provided inconsistent results. Methods: We performed a randomized, double-blinded, placebo-controlled trial of 5110 adults aged 50–84 years. In 2011–2012, participants were randomized to an initial oral dose of 200 000 IU vitamin D3 followed by 100 000 IU monthly (n = 2558) or placebo (n = 2552) until late 2013 (median follow-up, 1.6 years). Participants reported upper and lower ARIs on monthly questionnaires. Cox models analyzed time to first ARI (upper or lower) by treatment group. Results: Participants' mean age was 66 years and 58% were male; 83% were of European/other ethnicity, with the rest Maori, Polynesian, or South Asian. Mean (SD) baseline blood 25-hydroxyvitamin D [25(OH)D] level was 63 (24) nmol/L; 25% were <50 nmol/L. In a random sample (n = 441), vitamin D supplementation increased mean 25(OH)D to 135 nmol/L at 3 years, while those on placebo remained at 63 nmol/L. During follow-up, 3737 participants reported ≥1 ARI: 74.1% in the vitamin D group versus 73.7% in the placebo group. The hazard ratio for vitamin D compared with placebo was 1.01 (95% CI, 0.94, 1.07). Similar results were seen in most subgroups, including those with baseline 25(OH)D <50 nmol/L and in analyses of the upper/lower components of the ARI outcome. Conclusions: Monthly high-dose vitamin D supplementation does not prevent ARI in older adults with a low prevalence of profound vitamin D deficiency at baseline. Whether effects of daily or weekly dosing differ requires further study. Clinical Trials Registration: Australian New Zealand Clinical Trials Registry, identifier ACTRN12611000402943. Abstract : In a randomized, double-blinded, placebo-controlled trial of >5000 older adults in New Zealand, we found that monthly high-dose vitamin D supplementation did not prevent acute respiratory infection. Whether effects of daily or weekly dosing differ requires further study.